Expert and diagnostic criteria to identify the time death according to the study Achilles tendons in late postmortem period. - Povstyaniy, V. A. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Еestablishment of time of death is a core issue of forensic medicine. To solve this problem was proposed many different methods. They can provide answers regarding the death in the first 1-3 days post-mortem period. But after 3 days, because of of putrefaction corpse, the answer to this question is very difficult. At this time, has not found a precise criteria for the death of a few days postmortem period. Objective. Aim of the study was to determine the biochemical and biophysical parameters Achilles tendon in postmortem period. Methods. The material for the study was Achilles tendons of 22 corpses of people. For laboratory studies selected tendons only corpses of people, with accurately known period of death. Obtaining fluid from the tendon was performed by mechanical compression of the biological object in the press without homogenizing tissues. This fluid was stored at - 6-8 ° C. The liquid dissolved before use sterile isotonic solution in a ratio of 1: 4. Biochemical studies were performed using standard methods. Determined the amount of uric acid, urea, bilirubin, total protein, albumin, cholesterol, ALT, GGT and alkaline phosphatase. Made fixing Glow Discharge obtained from the Achilles tendon liquid. Results: In the liquid obtained from the Achilles tendon tissue, there is a change of the enzyme and other substances above. Individual enzymes increased in the 2-3 and 7-9 days after death. Total protein, urea and uric acid increased greatly to the 9-th day after decreased sharply. There have been analyzed the relationships identified components. They have significant differences that depend on the time of death. graphs of the number of separate components of the liquid and the intensity of the glow it gives can quickly determine which term death, depending on the type of graph belongs separate sample of fluid. Conclusion. Established by biochemical changes in individual components of fluid from connective tissue, can be used to determine the limitations of death. Assessment of the biological object by registering glow can be used to determine the death in late post-mortem period. For comparative analysis should be used graphic images.